2015
DOI: 10.1080/17470218.2014.961935
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking volitional control over task choice in multitask environments: Use of a stimulus set selection strategy in voluntary task switching

Abstract: Under conditions of volitional control in multitask environments, subjects may engage in a variety of strategies to guide task selection. The current research examines whether subjects may sometimes use a top-down control strategy of selecting a task-irrelevant stimulus dimension, such as location, to guide task selection. We term this approach a stimulus set selection strategy. Using a voluntary task switching procedure, subjects voluntarily switched between categorizing letter and number stimuli that appeare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 56 publications
3
12
0
Order By: Relevance
“…Voluntary task switching is still associated with switch costs (Arrington & Logan, 2004), but the paradigm allows to investigate different research questions, for example, how long people will stick to one task before switching to the other task. In this context, introducing a temporal delay between two stimuli corresponding to different tasks (i.e., presenting one stimulus earlier than the other stimulus; SOA) has been shown to influence participants’ task decisions, such that they were more likely to select the task that corresponded to the first stimulus (Arrington, 2008; Arrington & Weaver, 2015). In a similar vein, Mittelstädt, Miller, and Kiesel (2018) used increasing SOAs to introduce increasing costs the longer participants repeated one task in a voluntary task switching design.…”
Section: Discussionmentioning
confidence: 99%
“…Voluntary task switching is still associated with switch costs (Arrington & Logan, 2004), but the paradigm allows to investigate different research questions, for example, how long people will stick to one task before switching to the other task. In this context, introducing a temporal delay between two stimuli corresponding to different tasks (i.e., presenting one stimulus earlier than the other stimulus; SOA) has been shown to influence participants’ task decisions, such that they were more likely to select the task that corresponded to the first stimulus (Arrington, 2008; Arrington & Weaver, 2015). In a similar vein, Mittelstädt, Miller, and Kiesel (2018) used increasing SOAs to introduce increasing costs the longer participants repeated one task in a voluntary task switching design.…”
Section: Discussionmentioning
confidence: 99%
“…The most typical finding of VTS studies is the repetition bias: Participants usually show a tendency to select the same task in trial n that they performed in trial n – 1 (e.g., Arrington & Logan, 2004; Jurczyk et al, 2019; Kessler et al, 2009). This repetition bias persists when using the common version of the VTS paradigm in which participants are instructed to randomly choose the tasks in each trial (e.g., Arrington & Logan, 2004; Arrington & Weaver, 2015; Demanet et al, 2010). The additional finding of switch costs (i.e., slower reaction times [RTs] and increased error rates when switching compared to repeating tasks) in these studies suggests that the cognitive costs that incurred when switching tasks are reflected in both task selection and task performance.…”
Section: Voluntary Task Selection and Performance In Task-switching Pmentioning
confidence: 99%
“…While research on switch costs captures a unique aspect of everyday multitasking, it neglects important factors other than performance. For example, when multitasking, it is often not only critical how to perform multiple tasks in rapid succession, but also relevant to select what task to perform in the first place ( Arrington & Weaver, 2015 ; Braun & Arrington, 2018 ; Kiesel & Dignath, 2017 ; Dignath, et al, 2015 ; Schuch & Dignath, 2020 ). Indeed, a rich research tradition on decision making provides evidence that people consider different costs and benefits for their decisions (i.e., Basten et al, 2010 ; Kool et al, 2010 ; Simen et al, 2009 ) and recent theoretical work suggests that such utility-based decisions also take into account performance costs in multitasking ( Shenhav et al, 2013 , Musslick et al, 2015 ; Shenhav et al, 2016 ; see also Schuch, et al, 2019 ).…”
mentioning
confidence: 99%
“…4 and 5 ; Mayr, & Bell, 2006 ). Moreover, Arrington ( 2008 ; see also Arrington & Weaver, 2015 ) showed that the voluntary task choice was influenced by stimulus availability. In two experiments participants had to decide between a letter (vowel/consonant) and a number (odd/even) judgment task.…”
mentioning
confidence: 99%